The influence of histone orthologues, histone variants and post-translational modifications on the structure and function of chromatin - Resch, Michael George, author; Hansen, Jeffrey C., advisor; Luger, Karolin, advisor (Colorado State University. Libraries, 2008)
Two meters of DNA is packaged into the nucleus of each eukaryotic cell in the form of chromatin. DNA wraps around a protein histone octamer to form a nucleosome, the fundamental repeating unit of chromatin. The highly basic histone octamer contains two copies each of H2A, H2B, H3 and H4 to form the protein core of the nucleosome. There is a dynamic interplay of accessibility which compacts DNA yet allows access for fundamental cellular processes like transcription and DNA replication. This thesis investigates how histone variants and post-translational modifications contribute to the level of chromatin compaction. I demonstrated that defined nucleosomal arrays made with histones from multiple species oligomerize at different concentrations of MgCl2. A comparison of endogenous and recombinant Drosophila melanogaster histone octamers showed that this is unlikely due to posttranslational histone modifications, but likely a result of subtle changes in the sequences constituting the histone tails and structured surface of the histone octamer. I investigated the effect of incorporation of the centromere specific H3 histone variant centromere protein - A (CENP-A) into nucleosomes and nucleosomal arrays. Despite the fact that CENP-A shares only 60% sequence homology within the structured domain of major-type H3 (15% in the N-terminal domain), CENP-A (together with the other three core histones) forms nucleosomes and condensed nucleosomal arrays comparable to major-type H3. Post-translational modifications (PTM) contribute to the regulation of chromatin structure. I have analyzed the effect of H3 lysine 56 acetylation on nucleosome structure and chromatin condensation. This modification was previously thought to disrupt nucleosome structure. I developed methods to enzymatically acetylate large amounts of H3 specifically at Lys 56, and demonstrated that histone octamers containing H3-K56Ac form canonical nucleosomes. However, nucleosomal array condensation is compromised by this particular PTM. Together, these studies suggest that even subtle variations in histone sequence or post-translational modifications result in differences in chromatin higher order structure.
Keywords: chromatin; histones; nucleosomes; posttranslational modifications; molecular biology